ChemInform Abstract: Synthesis of 4H‐Benz[de]anthracen‐4‐ones via 1, 2‐Addition of Metal Acetylides to Benzanthrone. Issue 33 (27th July 2016) - Umeda, Rui; Namba, Teruaki; Shimizu, Yuji; Nishiyama, Yutaka
Abstract: Title compounds (III) are easily synthesized by reaction of benzanthrone (I) with various lithium acetylides (II) followed by treatment with acidic silica gel under air.